Coming Out Process of a Transman on The Level of Family Communication, Peer Group, and Other Social Environment - Mario Maya Puspita S; Dr. Hapsari Dwiningtyas, S.Sos, MA (Interaksi Online, 2016)
The decision to coming out for a transsexual will be faced with a binary view of society, the negative stigma of transsexual, and the threat of violence to create conflict. Coming out for a transman is required to negotiate the conditions to people at various levels of communication that surrounds his life in order to be understood, accepted and treated as a gender identity that is believed to be more comfortable in communicating with the people around him. This study aims to analyze the process of coming out as a form of sexual identity negotiation conducted by a female to male transsexual (transman) who have transitioned physically. Starting from analyzing the process of coming out on the level of family communication, peer group, and other social environments, their responses after coming out, and how the environment can accept, adjust, and establish good communication with a transman. This study uses the Sexual Identity Negotiation theory that would explain the negotiation process conducted in an attempt to convey sexual identity in order to achieve the adjustment of the surrounding social environment. It also uses the theory of gender performativity from Judith Butler that describing the gender fluidity. This study uses Autoetnografi method, because the primary data from this study uses researcher‟s life experiences as a transman. This implies putting research into two roles at once, namely as a subject who conducted the research as well as the object under study. The results showed that sexual identity negotiation on family communication has a dynamic conflict turning point that keep on appearing and disappearing, at some point where there is a condoning of this conflict, however it will reach a point where the conflict is arise. While in the process of negotiating sexual identity on peer group communication, researcher has more female friends due to the feminine character and behavior despite positioning himself as a man from the beginning. The negotiation process on the peer group level is minimal conflict because the adjustment of both sides, the researchers present himselves well and friends keep the feeling of researchers to not hurt him. On the level of romantic relationship, researcher‟s feminine character and behavior makes a barrier to the relationship that always strained relations with heterosexual women so that the relationship was never durable.